Effects of functional training on physical and technical performance among the athletic population: a systematic review and narrative synthesis - Wensheng Xiao; Te Bu; Junlong Zhang; Haogang Cai; Wuyi Zhu; Xiaorong Bai; Lin Zhang; Soh Kim Geok (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The evidence indicates that functional training is beneficial for athletes’ physical and technical performance. However, a systematic review of the effects of functional training on athletes’ physical and technical performance is lacking. Therefore, this study uses a literature synthesis approach to evaluate the impact of functional training on the physical and technical performance of the athletic population and to extend and deepen the existing body of knowledge. Methods This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and the researchers performed a systematic search of five international electronic databases using the predefined terms "functional training" and "athletes" on 15th November 2023: Web of Science, CINAHL PLUS, PubMed, Scopus, and SPORTDiscus. A PICOS approach was used to identify the following inclusion criteria: (1) athletes, (2) a functional training program, (3) an active control group, (4) a measure of physical and/or technical performance, and (5) randomized controlled studies. A methodological quality assessment of the original research was conducted using the Physiotherapy Evidence Database (Pedro) scale. The review was performed using the PRIMSA guidelines and registered in PROSPERO (ID: CRD42022347943). Results Of the 1059 potentially eligible studies identified, 28 studies met the inclusion criteria. The studies included were conducted on 819 athletes from 12 different countries and were published between 2011 and 2023. The assessment was performed on the Pedro scale, and the mean Pedro score for the included studies was 5.57 (moderate quality, ranging from 4 to 10). The eligibility study reported on 14 different types of sports, with 22 studies focusing on physical performance and 11 studies focusing on technical performance. These studies have shown that functional training can significantly improve the physical and technical performance of athlete populations, but in some studies, no significant difference in the data was observed between groups. Conclusion Functional training is an effective training method for enhancing the physical and technical performance of athlete populations. However, no significant difference in the data was observed between the functional training groups and the regular training group, which may be due to the duration of the training program, the different training experiences of the athletes, and the different focuses of the training regimens. Therefore, future studies should focus on the physical and technical performance of different sports groups with different types and durations of functional training programs to expand the current evidence base.